Analysis of the demand for human resources management specialists on the Moscow labor market - R. A. Ashurbekov; T. V. Kuzminova (Вестник университета)
The article presents the results of an analysis of the demand for labor of personnel management specialists in Moscow according to the state as of  July 2021. It provides a brief overview of the leading world and Russian  employment sites. The correctness of using the HeadHunter website (hh.ru) for analysing the demand for HR specialists in the Moscow labor market has been substantiated. Based on the results of a preliminary analysis of positions offered to HR specialists in Moscow, a sample of 250 vacancies has been formed, on which the requirements of employers to applicants have been assessed. The analysis has been carried out for three large groups: for managers (directors) for personnel, chief (leading) specialists and specialists  (assistants). A Box Plot diagram has been constructed and analysed based on the salary proposals.